In-situ high-efficiency PM capture from motor vehicle exhaust based on self-powered ceramic porous triboelectric filter. (1st June 2022) - Chen, Dahao; Hao, Song; Xu, Chuanyong; Liu, Liqiang; Zhao, Leilei; Hong, Hongxin; Xu, Wenkai; Tang, Qunwei; Du, Xiaozhen; Yang, Xiya
Abstract: Air pollution has become a major environmental concern due to the large amount of air pollutants emitted from human activities such as traffic, industry, and power plants. In September 2020, China has made an ambitious commitment to achieve carbon neutrality by 2060, while the transport sector represents a significant source of China's greenhouse gas (GHG) emissions, developing strategies to work toward the deep decarbonization of the transport sector are critical to meet the goal of carbon neutrality. Herein, a self-powered ceramic porous brick triboelectric filter (CPB-TEF) filled with fluorinated ethylene propylene (FEP) pellets is developed toward in-situ high-efficiency PM capture from motor vehicle exhaust. Driven by the vibration of vehicle exhaust pipe, the PM in the exhaust can be captured through the tribo-static electric field generated between the FEP pellets and the ceramic porous brick. The registered tribo-static electric field and electrical output performances in single hole of the CPB-TEF are systematically investigated and optimized by controlling the weight of FEP pellets, vibration amplitude, vibration frequency and acceleration. Moreover, a staggered electrode connection is designed to collect the electrostatic charges more efficiently inspired by the finding of the electric field superposition effects of holes. A total V oc of 252 V can be delivered for the upper two rows by the CPB-TEF. In addition, finite element analysis is applied to simulate Karman vortex street phenomenon generated from the fluid velocity field and the electrical potential distribution. Finally, the filtration efficiency for PM1.0, PM2.5, PM4.0 and PM10 are systematically analyzed by comparing the efficiency with and without CPB-TEF under vibration with obtained optimal filtration efficiency of 93.11%, 93.5%, 93.63%, 93.08%, respectively. This device behaved stable and durable working performance under the field test by driving the vehicle at idle speed mode, which can be further incorporated into the exhaust pipe after simple cleaning process for sustainable applications. Graphical Abstract: In-situ high-efficiency PM capture from motor vehicle exhaust based on self-powered ceramic porous triboelectric filter ga1 Highlights: Self-powered ceramic porous brick triboelectric filter (CPB-TEF) is developed towards PM capture from vehicle exhaust. Staggered electrode connection is designed to collect the electrostatic charges with a V oc of 252 V achieved. Optimal filtration efficiency for PM1.0, PM2.5, PM4.0 and PM10 are 93.11%, 93.5%, 93.63%, 93.08% obtained by the CPB-TEF. CPB-TEF demonstrates excellent working stability, washability and reusability with filtration efficiency all above 90%.